Shifting cultivation in North East India: Social dimension, cross cultural reflection and strategies for improvement - P, PUNITHA; ANSARI, M A; PANDEY, DILEEP K; RAM, DAYA; DATT, SHIV; SHARMA, P K; AHEIBAM, MONIKA; JYOTHI, S S P; PRAKASH, N (The Indian Journal of Agricultural Sciences, 2018)
The shifting cultivation is an indigenous land use system widely prevalent and practiced in North East India. Around the globe, the tropical countries practise this form of land use called commonly as shifting cultivation or swidden or slash and burn agriculture. Being one of the dominant land use systems, shifting cultivation calls for investigation by the interested researchers and academicians. Hence, the purpose of the present endeavor is to analyze the basic social dimensions of shifting cultivation through interventions analysis of secondary information and strategies for improvement. The review lays focus on shifting cultivation in India and blending the accumulated experiences with those of other countries. The review takes into account social characteristics of the shifting cultivation, the underlying causes of the shifting cultivation, the Government of India initiatives and impacts to control the shifting cultivation, sustainability, livelihood and food security and the shifting trends in shifting cultivation and the strategies for livelihood improvement. The analysis reveals that the shifting cultivators have an intricate relationship with the land and have a strong affinity and respect towards the land as it is a way of life. The trends in shifting cultivation though depict some patterns of change but the data are highly varied. From the literature, it is observed that there is a transition taking place in the various countries in varied form from subsistence based system to dual economy. The jhum land use is debatable as the practice is criticized as an unscientific form of land use, which causes land degradation and ecosystem fragility. As a result, the region is experiencing colossal loss of vegetation cover and top fertile soils through erosion from steep slopes. Therefore, a significant, multidimensional strategy is required to transform the large scale agricultural degraded land from a financial and environmental liability to valuable assets. However, the systematic and detailed study needs to be conducted in the North Eastern Region on the social dimension of shifting cultivation and strategies for its improvement.